Optimum Water Use in Conservation Tillage for Wheat Cultivation (Bangladesh Journal of Agricultural Research, 2012)
Conservation tillage system offers numerous benefits over intensive tillage  system. This experiment was conducted on conservation tillage using zero tilldrill,  power tiller operated seeder (PTOS) and bed planter along with farmers  practice of tillage by rotary tiller under different irrigation levels at Wheat  Research Centre (WRC), Nashipur, Dinajpur. Irrigation water was applied by 5  irrigation levels at different growth stages of the crop. The irrigation levels were  I0 (No irrigation), I1 (17-21 DAS), I2 (17-21 DAS  + 50-55 DAS). I3 (17-21 DAS+ 50-55 DAS + 75-80 DAS), and I4 (17-21 DAS + 35-40 DAS + 50-55 DAS +  75 80 DAS). It was observed that the sowing cost was reasonably reduced than  that of the farmer's practice. Seasonal water use was less in PTOS than other  tillage methods. Grain yield was significantly affected by tillage methods. The  higher grain yield was found from PTOS, bed planting, and zero tillage than that  of farmer's practice. There was no significant difference within the interaction  effect of tillage methods and irrigations. The effect of irrigation level was found  highly significant on grain yield. Water use efficiency increased with decrease  of irrigation water use and decreased with increase of irrigation. Average yields  in all tillage methods under I1, I2, I3, and I4 irrigation levels were found to  increase by 33, 43, 52, and 51 percent, respectively, compared to that of I0. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11172 Bangladesh J. Agril. Res. 37(1): 27-37, March 2012